Optimum pumping configuration for l-band EDFA incorporating ASE Pump source - Adikan, Faisal Rafiq Mahamd; Noor, A.S.M.; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2004)
L-band gain improvement through usage of secondary pumping sources in the form of amplified spontaneous emission (ASE) was conducted. A simulation of the three-level rate equation that precedes the experimental approach provides a limited overview of the behavior of various inputs into the active medium-the erbium-doped fiber. Gain improvement as high as 6 dB was attained while incurring minimal noise figure penalty; in this case as low as 1 dB. For an L-band amplifier system employing ASE to improve gain, pumping the system counterdirectionally with ASE while the 980- or 1480-nm pumps are being used in a copropagating configuration would yield the best overall performance in terms of gain.